Study of Smartphone Attacks and Defenses (International Journal of Engineering and Computer Science, 2017)
While enabling interoperation with the Internet brings tremendous opportunities in service creation and information access, the security threat of the Internet also dauntingly extends its reach. In this paper, we wish to enlighten the community that the longrealized risk of interoperation with the Internet is becoming a reality. Smart-phones, interoperable between the telecom networks and the Internet, are dangerous conduits for Internet security threats to reach the telecom infrastructure. The damage caused by subverted smart-phones could range from privacy violation and identity theft to emergency call center DDoS attacks and national crises. We also propose techniques to generate solution space that includes smart-phone hardening approaches, Internet-side defense, telecom-side defense, and coordination mechanisms that may be needed between the Internet and telecom networks.